On Carlitz’s Type Modified Degenerate q-Changhee Polynomials and Numbers - Byung Moon Kim; Lee-Chae Jang; Wonjoo Kim; Hyuck-In Kwon (Discrete Dynamics in Nature and Society)
Recently, Dolgy-Jang-Kwon-Kim introduced Carlitz’s type q-Changhee polynomials. In this paper, we define Carlitz’s type modified degenerate q-Changhee polynomials and investigate some interesting identities of these polynomials.